2015
DOI: 10.1142/s2251237315400080
|View full text |Cite
|
Sign up to set email alerts
|

Competitive Self-Assembly Manifests Supramolecular Darwinism in Soft-Oxometalates

Abstract: Topological transformation manifested in inorganic materials shows manifold possibilities. In our present work, we show a clear topological transformation in a soft-oxometalate (SOM) system which was formed from its polyoxometalate (POM) precursor [PMo 12 @Mo 72 Fe 30 ]. This topological transformation was observed due to time dependent competitive self-assembly of two di®erent length scale soft-oxometalate moieties formed from this two-component host-guest reaction. We characterized di®erent morphologies by s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
1

Relationship

5
1

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…Such vesicle-like super-structure formation of the metal oxide clusters is well known and studied by our group and we have proposed them to be called so-oxometalates (SOMs). [43][44][45][46][47][48][49][50] Very recently we have exploited various properties of SOMs and thereby, their usability in a large range of applications have been explored. SOMs can undergo topological transformation, 51 can be used in patterning 52,53 and as active particles.…”
Section: Introductionmentioning
confidence: 99%
“…Such vesicle-like super-structure formation of the metal oxide clusters is well known and studied by our group and we have proposed them to be called so-oxometalates (SOMs). [43][44][45][46][47][48][49][50] Very recently we have exploited various properties of SOMs and thereby, their usability in a large range of applications have been explored. SOMs can undergo topological transformation, 51 can be used in patterning 52,53 and as active particles.…”
Section: Introductionmentioning
confidence: 99%
“…The immobilization of the POM moiety on the electro active surface can enhance the catalytic activity of these materials ,. POMs can also exist in a colloidal state of soft‐oxometalates (SOMs) . We have recently shown that soft oxometalates based on several different oxometalates can act as active catalyst for photo chemical oxidation of water without the need of a photosensitizer and a sacrificial electron donor ,…”
Section: Introductionmentioning
confidence: 99%
“…[24,[26][27][28][29] POMs can also exist in a colloidal state of softoxometalates (SOMs). [30][31][32][33] We have recently shown that soft oxometalates based on several different oxometalates can act as active catalyst for photo chemical oxidation of water without the need of a photosensitizer and a sacrificial electron donor. [26-27,34À 37] Further CO 2 can be transformed into other energy dense organic compounds like formic acid and formaldehyde by H 2 O in presence of light using SOMs.…”
Section: Introductionmentioning
confidence: 99%
“…Designing of the catalyst materials using 3d-transition metal-based ions makes the process inexpensive, and with this end in view in our present work we synthesized a copper tungsten oxide {[K 6.5 Cu­(OH) 8.5 (H 2 O) 7.5 ] 0.5 [K 3 PW 12 O 40 ]}-based softoxometalate. The material is chosen such that the tungsten cores, especially PW 12 cores, are photoactive and these tungsten cores serve as very active catalyst for photochemical water oxidation reaction. , Tungsten cores also make the overall metal oxygen framework robust and stable in a photochemical environment. It is also known that Cu-based material, especially Cu-based inorganic complexes, , as well as copper oxide-based nanomaterials are also very effective for carbon dioxide reduction reaction.…”
Section: Introductionmentioning
confidence: 99%